2022
DOI: 10.1021/acsinfecdis.2c00249
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging of Active Invasive Fungal Infections with d-[5-11C]-Glutamine

Abstract: The increasing prevalence and severity of invasive fungal infections (IFIs), especially in immunocompromised populations, has amplified the need for rapid diagnosis of fungal pathogens. Radiotracers derived from D-amino acids (DAAs) show promise as bacterial-specific positron emission tomography (PET) imaging agents due to their preferential consumption by bacteria and largely nonutilization by hosts. Unlike mammals, fungi can utilize external DAAs including D-glutamine for their growth by rapidly upregulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…[54] The study found that in a dual infection mouse myositis model, PET imaging based on infections. [55] These data provide robust evidence for the clinical promise of D-amino acid-based PET tracers for imaging active infections in human. It's important to note that there may be a potential concern for high background uptake in some organs with rich microbiome, such as the gastrointestinal tract.…”
Section: Pet Imagingmentioning
confidence: 66%
“…[54] The study found that in a dual infection mouse myositis model, PET imaging based on infections. [55] These data provide robust evidence for the clinical promise of D-amino acid-based PET tracers for imaging active infections in human. It's important to note that there may be a potential concern for high background uptake in some organs with rich microbiome, such as the gastrointestinal tract.…”
Section: Pet Imagingmentioning
confidence: 66%
“…The study found that in a dual infection mouse myositis model, PET imaging based on [ 11 C]‐D‐Gln could detect infections induced by E. coli and MRSA with low uptake in sterile inflammation site and background tissue. The group also used [ 11 C]‐D‐Gln for imaging fungal infections [55] . These data provide robust evidence for the clinical promise of D‐amino acid‐based PET tracers for imaging active infections in human.…”
Section: Pathogenic Bacteria‐targeted Diagnostics and Therapymentioning
confidence: 85%
“…Previous work has shown that numerous exogenous d -amino acids can be incorporated into peptidoglycan, including d -methionine, d -phenylalanine, d -tryptophan, and d -valine . In addition, another carbon-11 PET infection imaging strategy used d -[3- 11 C]­glutamine. , Derivatives of these d -amino acids, therefore, represent additional routes for bioorthogonal bacterial detection using PET.…”
Section: Discussionmentioning
confidence: 99%